2004
DOI: 10.1080/08880010490477248
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Acute Lymphoblastic Leukemia Presenting as Sever Hypercalcemia

Abstract: A 9-year-old girl presented at the Pediatric Emergency Department with an acute onset of gastrointestinal symptoms due to hypercalcemia. Despite the absence of circulating blast, bone marrow biopsy was diagnostic of acute lymphoblastic leukemia. The hypercalcemia was initially treated with intravenous hydration and furosemide, and later on with bisphosphonates. However, the serum calcium levels normalized only after the beginning of specific chemotherapy. Hypercalcemia represents an emergency in children, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 15 publications
0
1
0
1
Order By: Relevance
“…Conversely, BPs do not always successfully control the hypercalcaemia. Buonuomo et al (2004) reported a case of a 9‐year‐old patient who presented with hypercalcaemia complicated by acute pancreatitis that was refractory to rehydration, forced diuresis and intravenous clodronate therapy. Once the diagnosis of ALL was established, specific chemotherapy was commenced resulting in normalization of calcium within 72 h. Hypercalcaemia that was refractory to five doses of pamidronate in a case of T‐cell ALL was successfully treated with induction chemotherapy (Unal et al , 2008).…”
Section: Bisphosphonates In Childrenmentioning
confidence: 99%
“…Conversely, BPs do not always successfully control the hypercalcaemia. Buonuomo et al (2004) reported a case of a 9‐year‐old patient who presented with hypercalcaemia complicated by acute pancreatitis that was refractory to rehydration, forced diuresis and intravenous clodronate therapy. Once the diagnosis of ALL was established, specific chemotherapy was commenced resulting in normalization of calcium within 72 h. Hypercalcaemia that was refractory to five doses of pamidronate in a case of T‐cell ALL was successfully treated with induction chemotherapy (Unal et al , 2008).…”
Section: Bisphosphonates In Childrenmentioning
confidence: 99%
“…Diversos autores han manifestado que, en casos de hipercalcemia grave refractaria en el contexto de síndrome paraneoplásico, la normalización de la calcemia solo se alcanzó tras establecer el tratamiento citostático específico. [10][11][12] Por ello, ante la persistencia de cifras de calcio plasmáticas elevadas en nuestro paciente, se optó por iniciar un tratamiento quimioterápico urgente empírico tras la obtención de muestras de biopsia diagnósticas, y se observaron, posteriormente, cifras de calcio plasmático normales.…”
Section: Figura 3 Evolución De Los Niveles De Calcio Plasmático En Runclassified